Beyond Distribution: Critique of Spatial Justice Theories—Case Study of Shanghai’s 15-Minute City - Shengxi Xin; Qingyuan Guo (Land)
The concept of the 15-minute city is increasingly being adopted globally as a pathway towards the vision of a just city. However, this distributive justice-based discourse is also used to justify and depoliticize radical planning interventions, particularly relocation, which profoundly impact the lifeworlds of affected individuals. Despite improved accessibility and the reallocation of resources, relocatees’ perceived injustice persists. This study aims to address a critical question: How does relocation planning impact the lifeworlds of affected communities, and how does this contribute to the sense of injustice experienced by relocatees? The theoretical framework we used critically examines spatial justice theories, emphasizing their inherent “logic of equation”, which reduces people’s complex lived experiences and subjective realities to measurable data and numbers, thereby disrupting individuals’ lifeworlds. Empirically, this study conducted a case study of a relocation project in Shanghai’s inner city, utilizing mind mapping to visualize the spatial perceptions and activities of 15 residents before and after relocation, complemented by interviews with these residents and two planning officials. While the planners’ evaluations indicate improved built environments post relocation, the findings reveal significant disruptions to the residents’ socio-spatial networks, particularly among the elderly. These disruptions diminished their capacity and willingness to engage with the new space, fostering a persistent sense of injustice. This study concludes that addressing planning disruptions requires policies that go beyond material redistribution to restore and reshape people’s lifeworlds.